Development of Students Worksheet Nuanced of Emotional Spiritual Quotient about Cell, Organ, Tissue and Organism for Seventh Grade Students of SMP/MTs - Ghean Azrin Mirza; Ristiono Ristiono; Dezi Handayani (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2019)
Education is a conscious effort to improve the quality of learners both from aspects of science, attitude, and skills. During this school education focuses on the development of intellectual intelligence (IQ), which absorbs as much science but not yet touched on emotional intelligence (EQ) and spiritual (SQ). These three potentials should have been integrated in biology learning. Based on the results of research that has been done, the product results are LKPD nuanced ESQ on the cell material for students of grade VII SMP / MTs. Result of validity test with value of 81,37% by validator fulfill valid criterion, Result of validity in terms of feasibility of content, language, presentation and graphics. Practical test result with 92,53% value by teacher with very practical criteria from ease of use, time efficiency and forgiveness, while the result of practical test by student with 82,65% practical criterion from convenience, and benefit.